19. Comparison of myocardial blood flow estimates from dynamic contrast-enhanced used in Cardiac Magnetic Resonance Imaging. (December 2018) - Carnı̀, M.; Borrazzo, C.; Galea, N.; Vullo, F.; Francone, M.; Catalano, C.; Carbone, I.; Pacilio, M.
Abstract : Purpose: Dynamic Contrast-Enhanced Cardiovascuar Magnetic Resonance Imaging (DCE-CMRI) may quantitatively assess the Myocardial Blood Flow (MBF), recovering the tissue impulse-response function to transit of gadolinium bolus through myocardium. Several deconvolution techniques are available, using various models for the impulse-response[1] . The method choice may influence the results, producing differences that have not been deeply investigated yet. Methods: Three methods for quantifying myocardial perfusion were compared: Fermi Function Modeling, Tofts Model, and Gamma Function model, the latter traditionally used in brain perfusion. Thirty human subjects were studied at rest, and Cold Pressor Test stress, injecting a single-bolus of gadolinium of 0.1 mmol/kg. Perfusion estimate differences among methods were analysed by paired comparisons with Student's t-test, linear regression analysis, and Bland-Altman plots, and using also the two-way ANOVA, considering the MBF values of all patients grouped according to two categories: calculation method and rest/stress conditions. Results: Perfusion estimates obtained by various methods in both rest and stress conditions were not significantly different, and in agreement with the literature. Results obtained during the first-pass transit time (20 s) yielded p-values in the range 0.20–0.28 for the Student's t-test, slopes from the linear regression analysis between 0.98–1.03, and R values between 0.92–1.01. With the two-way ANOVA, the results were p = 0.20 for the method effect (not significant), p < 0.0001 for the rest/stress condition effect, whereas no interaction resulted between rest/stress condition and method (p = 0.70, not significant). Considering a wider period (60 s), the estimates for both rest and stress conditions were 25–30% higher than those obtained in the 20 s period. Conclusion: MBF estimates obtained by various methods at rest/stress condition were not significantly different in the first-pass transit time, encouraging quantitative perfusion estimates in DCE-CMRI with the used methods.